UPAYA PENCIPTAAN WIRAUSAHA MAPAN MELALUI SANGGAR ABYAKTA UNTUK PENGUATAN USAHA PADA USAHA RINTISAN DI DESA GENITO KABUPATEN MAGELANG - Nurkhasanah, Nurkhasanah; Pramudianti, Ulfa Rahma; Sarifah, Siti; Chasanah, Hikmah Rochimatul; Amini, Nurul Fajar; Maknun, Lu'lu'ul; A'yun, Qurotul; Kautsar, Akhmad; Baroroh, Erli; Ramadani, Cahya; Nugroho, Bondan; Ningsih, Nur Cahyati; Kariza, Alifia Ninda; Anjani, Arlian Sherly; Panjawa, Jihad Lukis (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
Entrepreneurial village as an alternative forum in realizing community welfare through innovation with local resources and potential owned by the village. Business actors in the village are an important element in creating an entrepreneurial village. Start-up entrepreneurs often face the same problems in achieving an established business. The aim of this program is to create established entrepreneurs by strengthening start-up businesses in Genito Village, Magelang Regency. The methods used include outreach and mapping, training and mentoring and expos. The results show that the understanding of start-up entrepreneurs is still at a basic level and has different problems from the mapping results. A forum has been formed in the form of the Sanggar Abyakta to create a pioneering entrepreneurial village. Apart from that, basic management training and assistance, halal certification and marketing have real efforts in strengthening start-up businesses. Expos/exhibitions have an important role in introducing start-up business products. Follow-up is needed regarding information on access to finance and understanding in production capacity in meeting market needs that need to involve other stakeholders.